2019
DOI: 10.1016/j.pbiomolbio.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser therapy (LLLT) modulates ovarian function in mature female mice

Abstract: Low level laser therapy (LLLT) modulates ovarian function in mature female mice, Progress in (2018), ABSTRACT 22 It is known that LLLT has beneficial effects on several pathological conditions including 23 wound healing, pain and inflammation. LLLT modulates biological processes, including 24 cell proliferation, apoptosis and angiogenesis. In the present study, we examined the effect 25 of local application of LLLT on follicular dynamics, ovarian reserve, AMH expression, 26 progesterone levels, apoptosis, angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Finally, photobiomodulation therapy (PBMT) with low-level laser light therapy (LLLT) is known to exert its rejuvenative effects via targeting the chromophore cytochrome C oxidase in mitochondrial membrane (119). In two rodent studies, PBMT is shown to increase the number of primary and pre-antral follicle count (120,121), to decrease granulosa cell apoptosis and to increase angiogenesis; however, it was not shown to increase the number of Pfs (120).…”
Section: Mitochondrial-targeting Therapiesmentioning
confidence: 99%
“…Finally, photobiomodulation therapy (PBMT) with low-level laser light therapy (LLLT) is known to exert its rejuvenative effects via targeting the chromophore cytochrome C oxidase in mitochondrial membrane (119). In two rodent studies, PBMT is shown to increase the number of primary and pre-antral follicle count (120,121), to decrease granulosa cell apoptosis and to increase angiogenesis; however, it was not shown to increase the number of Pfs (120).…”
Section: Mitochondrial-targeting Therapiesmentioning
confidence: 99%